POTENSI LIMBAH IKAN LELE (Clarias sp.) SEBAGAI SUMBER KOLAGEN ALAMI UNTUK APLIKASI FARMASI DAN KOSMETIKA: KAJIAN LITERATUR - Zuriati Uno, Wiwit; Djamil, Cahniar; Alvionita, Mita; Pratiwi Iman, Dian (Jurnal Multidisipliner Bharasumba, 2024)
Catfish (Clarias sp.) waste, which includes bones, skin, and scales, represents a potential natural source of collagen with significa nt economic value. Collagen plays an important role in pharmaceuti cal, cosmetic, and functional food industries due to its bioactive proper ties such as antioxidant, antimicrobial, and tissue-regenerative capabil ities. This literature review aims to explore the potential utilization of catfish waste as a collagen source and its possible combination with bioactive plants, such as Moringa oleifera, Hibiscus sabdariffa, or mic roalgae, to enhance biological activity & formulation stability. The rev iew indicates that acid & enzymatic extraction methods are the most eff ective techniques for obtaining high-quality collagen from catfish was te. Recent studies reveal that catfish collagen possesses an ami no acid composition similar to mammalian collagen, with high levels of glycine & proline. Furthermore, combining catfish collagen with bio active pla nt extracts enhances antioxidant & antidiabetic properties. This study highlights that collagen development from catfish was teoffe rs an inno vative, eco-friendly biotechnological approach aligned with circular economy principles & great potential for value prod uct development.